Upaya Guru dalam Meningkatkan Motivasi Belajar Siswa di Sekolah Minggu Buddha (SMB) Dhamma Sena (Studi Kasus di Vihara Sradha Dhamma Pokoh, Wonoboyo) - Tri Dian Ayu; Dwi Maryani Rispatiningsih; Walyono Walyono (Ideas Publishing, 2022)
Motivation is a factor that must be included in the learning process so that the learning process can be successful.This article was written with the aim of describing how to increase students motivation by using strategies such as making miniatures at the Buddhist Sunday School (SMB), and to find out the obstacles and provide insight into students beliefs about Buddhism. The researcher uses case study qualitative method, data collection method uses observation, interview and documentation. The location of this research is the Budddhist Sunday School (SMB) Dhamma Sena, Vihara Sradha Dhamma, Pokoh, Wonoboyo, Wonogiri Regency. The subject of this study, namely the Buddhist Sunday School (SMB) teacher, as well as elementary school Sunday School students. The results of this study, namely the teacher s efforts in increasing student learning motivation are using gifts/reward, using interesting learning media, appropriate strategies such as using the case study method, carrying out outbound activities or outdoor activities, and a comfortable study room that is not cluttered.